UNIFIED LAWYERS EXAMINATION, FOR AND AGAINST - Gaveika, Artūrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Ministry of Justice of the Republic of Latvia believes that in Latvia is relatively low quality of legal education. As the most appropriate way for solving this problem is considered state unified lawyer qualification exam, which would promote legal education quality growth. The quality of legal education in Latvia is increasingly becoming the subject of public discussion. In 2016 took place the final Ministry of Justice working group meeting on implementation of the state lawyer's professional qualification examination. The article devoted to challenges and perspectives of unified lawyer qualification examination implementation.